2019
DOI: 10.3346/jkms.2019.34.e134
|View full text |Cite
|
Sign up to set email alerts
|

New Termination-of-Resuscitation Models and Prognostication in Out-of-Hospital Cardiac Arrest Using Electrocardiogram Rhythms Documented in the Field and the Emergency Department

Abstract: Background Electrocardiogram (ECG) rhythms, particularly shockable rhythms, are crucial for planning cardiac arrest treatment. There are varying opinions regarding treatment guidelines depending on ECG rhythm types and documentation times within pre-hospital settings or after hospital arrivals. We aimed to determine survival and neurologic outcomes based on ECG rhythm types and documentation times. Methods This prospective observational study of 64 emergency medical cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 22 publications
(53 reference statements)
0
43
1
Order By: Relevance
“…3). 11,17,18,33,36,37,39,40 The pooled specificity and sensitivity for all studies were 0.98 (0.96À0.99) and 0.27 (0.23À0.30), respectively. The pooled PPV and NPV were 1.00 (0.99À1.00) and 0.05 (0.03À0.08), respectively.…”
Section: Als Tor-rulementioning
confidence: 93%
See 1 more Smart Citation
“…3). 11,17,18,33,36,37,39,40 The pooled specificity and sensitivity for all studies were 0.98 (0.96À0.99) and 0.27 (0.23À0.30), respectively. The pooled PPV and NPV were 1.00 (0.99À1.00) and 0.05 (0.03À0.08), respectively.…”
Section: Als Tor-rulementioning
confidence: 93%
“…Nine studies reported on 173.224 patients. 11,12,17,19,33,36,37,39,40 Test characteristics and forest plots are shown in Fig. 3.…”
Section: Bls Tor-rulementioning
confidence: 99%
“…Fortunately, recent cardiopulmonary resuscitation (CPR) guidelineswere changed, recommendingthat all healthcare providers assess the safety of the scene and wear higher levels of PPE for protection against infectious airborne dropletsand detailing the criteria for the basic life support termination of resuscitation (BLS-TOR) rule. These guidelines stated that before terminating resuscitative efforts, the healthcare workers must check that 1) the arrest was not witnessed byemergency medical service (EMS) personnel or a rst responder,2)ROSC was not observed prior to the patient being transported to the emergency medical centre (EMC), and 3) no electrical shocks were delivered [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…We applied the rules that were typically selected depending on the country or region where the derivation and validation phaseswere conducted.These included the(1) International BLS and advanced life support (ALS) rules derived and validated in the United States and Europe [8], (2) Goto and KANTO-SOS rules developed in Japan and Asian countries [13,14], and (3) Korean OHCA registry-based TOR models,Korean Cardiac Arrest Research Consortium (KoCARC) TOR rules, and two new TOR models, whichwere used in our previous studies [7,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation